Facile Synthesis of Nanoporous Amorphous Silica on Silicon Substrate. (14th July 2020) - Hui, Luo; Yongquan, Huang; Lili, Wu; Yanming, Ge; Kaichen, Huang; Xi, Lin; Kexin, Tang; Xiufang, Lv; Hailing, Yu
Abstract : Large-scale nanoporous amorphous silica nanostructure is fabricated via a simply etched approach and effective thermal evaporation process. The nanoporous amorphous silica was synthesized by a general and scalable process via etching by metal particles on the silica sheets. In this study, we elucidated how a nanoporous structure was performed and the addition of indium is the key factor that determined the formation of the nanoporous structures. The morphology and the sizes of the porous structure could be tunable by the sizes and the shape of the metal. We discovered a promising optical property in the as-synthesized nanostructures, which have a photoluminescence in an intensive ultraviolet emission as well as a broad visible emission at room temperature.